2020
DOI: 10.1002/adhm.202000469
|View full text |Cite
|
Sign up to set email alerts
|

Onion Epithelial Membrane Scaffolds Transfer Corneal Epithelial Layers in Reconstruction Surgery

Abstract: Plants and their extracts have been used especially in China for more than ten centuries for preventing and treating disease. However, there are only few reports describing their use in animal cell culture and tissue transplantation. In this study, onion epithelial membranes (OEM) is used as scaffolds to support cultures of a variety of cells such as fibroblasts and epithelial cells notably; they maintain the phenotypic characteristics of corneal epithelial cells. This improvement includes preservation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The current study assessed the ability of topical onion juice to ameliorate age-related corneal changes based on histopathological, immunohistochemical and histomorphometric examinations. Despite their limited number, previous experimental studies assessed the effects of onion extracts on corneal changes related to different animal models [18,28], in addition to the effects of onion extracts on the pathological changes of other ocular structures [19,29,30]. Furthermore, several publications indicated that age has major changes on the cornea [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The current study assessed the ability of topical onion juice to ameliorate age-related corneal changes based on histopathological, immunohistochemical and histomorphometric examinations. Despite their limited number, previous experimental studies assessed the effects of onion extracts on corneal changes related to different animal models [18,28], in addition to the effects of onion extracts on the pathological changes of other ocular structures [19,29,30]. Furthermore, several publications indicated that age has major changes on the cornea [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the disadvantages of HAM (such as high thickness, variable transparency, biodegradation and immunosuppression), it is urgent for us to find alternative cell carriers/scaffolds to substitute for HAM. At present, alternative cell carriers/scaffolds contain modified HAM, collagen[ 159 , 160 ], fibrin[ 161 ], siloxane hydrogel contact lenses, human lens capsules, poly (ε-caprolactone)[ 162 ], onion epithelial membrane scaffolds[ 163 ], carboxymethyl cellulose (CMC)[ 164 ], electrospun polycaprolactone/gelatine nanocomposites[ 165 ] and other emerging materials. The modified HAM will be described in detail below.…”
Section: Corneal Epithelial Stem Cellsmentioning
confidence: 99%